Sensitivity studies for the main r process: β-decay rates - M. Mumpower; J. Cass; G. Passucci; R. Surman; A. Aprahamian (AIP Advances, 2014)
The pattern of isotopic abundances produced in rapid neutron capture, or r-process, nucleosynthesis is sensitive to the nuclear physics properties of thousands of unstable neutron-rich nuclear species that participate in the process. It has long been recognized that the some of the most influential pieces of nuclear data for r-process simulations are β-decay lifetimes. In light of experimental advances that have pushed measurement capabilities closer to the classic r-process path, we revisit the role of individual β-decay rates in the r process. We perform β-decay rate sensitivity studies for a main (A > 120) r process in a range of potential astrophysical scenarios. We study the influence of individual rates during (n, γ)-(γ, n) equilibrium and during the post-equilibrium phase where material moves back toward stability. We confirm the widely accepted view that the most important lifetimes are those of nuclei along the r-process path for each astrophysical scenario considered. However, we find in addition that individual β-decay rates continue to shape the final abundance pattern through the post-equilibrium phase, for as long as neutron capture competes with β decay. Many of the lifetimes important for this phase of the r process are within current or near future experimental reach.